Narrative Review of Ligamentous Wrist Injuries - Margulies, Ilana G.; Xu, Hope; Gopman, Jared M.; Freeman, Matthew D.; Dayan, Etan; Taub, Peter J.; Melamed, Eitan (Journal of Hand and Microsurgery, 2021)
Ligamentous wrist injuries are common occurrences that require complex anatomical mastery and extensive understanding of diagnostic and treatment modalities. The purpose of this educational review article is to delve into the most clinically relevant wrist ligaments in an organized manner to provide the reader with an overview of relevant anatomy, function, clinical examination findings, imaging modalities, and options for management. Emphasis is placed on elucidating reported diagnostic accuracies and treatment outcomes to encourage evidence-based practice.
Keywords: wrist ligaments; wrist injuries; wrist ligament anatomy; diagnostic modalities